Evaluation of prescribing patterns of teaching and non teaching hospitals by undergraduate medical students in Pune, India - Pillay, Anjali; Keche, Yogendra; Yegnanarayan, Radha; Patil, Vaibhav; Patil, Gargi; Dangare, Renuka (International Journal of Basic & Clinical Pharmacology, 2017)
Background: This study was carried out in various hospitals to analyze the use of rational fixed dose combinations (FDCs) in Pune. Methods: 279 prescriptions were evaluated in this study. Information about age, sex, names of the all the drugs prescribed by doctor/ physician, diagnosis for the use of prescriptions and adverse effects were noted in the audit form from the prescriptions of the patients. Rationality of fixed dose combination is evaluated according to WHO Model List of Essential Drugs, 17th updated version, 2011. Results: 56.98 % doctor’s prescriptions in this study were containing of fixed dose combinations and out of this 10.69 % prescriptions were including two or more FDCs in their prescriptions. Only 13.20% FDCs were in accordance with WHO Model List of Essential Drugs. FDCs from antiinflammatory and antirheumatic products, vitamins, minerals, antianaemic preparations, drugs for acid related disorders, antibacterials for systemic use and cough and cold preparations were used more by private non teaching hospitals as compared to SKNMC & GH teaching hospital. 64.61 % prescriptions of private hospitals and 34.08 % prescriptions of teaching hospital were containing more than one drug. Conclusions: This study has shown that about every alternate prescription contains FDC. More than 80 % of prescribed FDCs are not in accordance with Essential Drugs List. Vitamins, minerals, antianaemic preparation FDCs should be prescribed judiciously as they are not free from ADRs. More number of drugs (poly-pharmacy) and FDCs were prescribed by non teaching private hospitals.